Experiments in skin : race and beauty in the shadows of Vietnam - Tu, Thuy Linh N. (Duke University Press, 2021)
"Thuy Linh Nguyen Tu examines the legacies of the Vietnam War on contemporary ideas about race and beauty, showing how US wartime efforts to alleviate the environmental and chemical risks to soldiers' skin has impacted how contemporary Vietnamese women use pharmaceutical cosmetics to repair the damage from the war's lingering toxicity."--